Life Cycle Assessment of Geothermal Power Technologies for Indonesia’s Energy Transition: A Review of Environmental Hotspots and Optimization Strategies - Rajagukguk, Vania Larissa; Dahlan, Astryd Viandila (Indonesian Journal of Multidisciplinary Science, 2025)
Indonesia has set a target to achieve Net Zero Emissions (NZE) by 2060 and a 52% renewable energy share by 2030. Geothermal energy, with 29.5 GW potential, is critical, yet environmental performance of technologies remains poorly characterized, hindering sustainable decisions. This systematic review analyzes life cycle assessment (LCA) studies on binary, flash, and dry steam geothermal technologies. Scopus and Google Scholar searches using keywords "geothermal power plant" and "life cycle assessment" yielded 30 studies (2013–2025). Environmental burdens vary by technology, geology, design, and operations. Binary systems face high impacts from drilling, steel construction, and working-fluid leakage (up to 64% of global warming potential). Flash systems show major CO? and H?S emissions, reducible by 78% via abatement or hybrid flash-binary setups. Dry steam plants are dominated by non-condensable gas (NCG) emissions unless hybridized with Enhanced Geothermal Systems (EGS) or Combined Heat and Power (CHP), shifting hotspots to construction. Findings offer Indonesia actionable insights: select cleaner configurations, optimize drilling, deploy emission controls, and prioritize low-global-warming-potential fluids. This synthesis of site-specific LCAs creates a framework identifying hotspots and pathways, supporting evidence-based policies for sustainable geothermal expansion in Indonesia's energy transition.